MULTILINGUALISM AND MEANING-MAKING IN THE SOEDS CAFÉ MENUS : A MULTIMODAL DISCOURSE ANALYSIS - Kholifah, Asrofin Nur; Sholikhah, Ika Maratus; Wardani, Erna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study explores how multilingualism and multimodal resources are employed in the menu of The Soeds Cafe to construct meaning, identity, and consumer appeal. Using the framework of Kress & van Leeuwen multimodal discourse analysis and Backhaus linguistic landscape studies, the research examines the interplay between linguistic choices and visual design in shaping the communicative function and branding strategy of the menu. The analysis reveals that English is used symbolically to convey cosmopolitan modernity, while Indonesian reinforces cultural relevance and local authenticity. Each section of the menu presents a curated linguistic and visual identity: the Butter Rice page juxtaposes global dish names with Indonesian flavor profiles, the Cocoa Series highlights regional pride and artisanal appeal, and the Pastas section demonstrates playful hybridity. These findings show that menus serve as performative texts, reflecting broader discourses of globalization, localization, and sociocultural aspiration in public food spaces.